Energetic demands of interchange and full-match rugby league players - Cummins, C. J.; Gray, A. J.; Shorter, K. A.; Halaki, M.; Orr, R. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to describe and compare the metabolic demands of rugby league for interchange and full-match players in relation to positional groups. Eighteen elite rugby league players were recruited. A time-motion model was used to estimate the energy expenditure and metabolic demands of rugby league match-play using Global Positioning System (GPS) technology. This approach uses players' GPS velocity-time curves to examine running velocity. Players were categorized into positional groups (outside backs, adjustables, wide-running, and hit-up forwards) and then further categorized into full-match or interchange players. Compared with their full-match counterparts, interchange wide-running forwards expended greater energy (43.1 ± 6.1 vs. 28.6 ± 7.5 kJ/kg, p = 0.001, effect size [ES] = -2.38) and produced a higher anaerobic index (p = 0.016, ES = 0.56) and mean power (7.4%, p = 0.003, ES = 0.66) per match. Full-match adjustables expended 94.8% more energy (p = 0.001, ES = -2.3) and performed more moderate accelerations (10.1%, p = 0.014, ES = -0.57) and decelerations (7.6%, p = 0.017, ES = -0.8), than their interchange counterparts. Outside backs did not interchange and hit-up forwards rarely (n = 2) played an entire match. Differing metabolic demands were identified for interchange and full-match players across positional groups, suggesting position-specific conditioning drills are required to model the energetic demands of match-play.